The Role of Metacognitive Knowledge in Learning, Teaching, and Assessing - Pintrich, Paul R. (Theory into practice, 2002)
[...]these strategies can be used across a large number of different tasks and domains, rather than being most useful for one particular type of task in one specific subject area (e.g., solving a quadratic equation in mathematics, applying Ohm's law in science). [...]of these conversations, teachers will become aware of the general level of metacognitive knowledge in their classrooms and will be able to judge fairly quickly the level and depth of students' metacognitive knowledge. [...]more formal questionnaires and interview procedures can be used to assess students' metacognitive knowledge concerning their learning strategies as well as their knowledge about different tasks and contexts (see Baker & Cerro, 2000; Pintrich et al., 2000). [...]self-knowledge is a critically important component of metacognitive knowledge. Because metacognitive knowledge in general is positively linked to student learning, explicitly teaching metacognitive knowledge to facilitate its development is needed.